THE EFFECT OF POROSITY ON FATIGUE CRACK INITIATION AND PROPAGATION IN AM60 DIE-CAST MAGNESIUM ALLOY - Yang, Zhuofei (My University, 2015)
The AM60 Mg alloy has been used in the automotive industry to help achieve higher fuel efficiency. However, its products, mostly fabricated via high pressure die casting process, are inherently plagued with porosity issues. The presence of porosity impairs mechanical properties, especially fatigue properties, and thus affects the product reliability. We have therefore studied the effect of porosity on the fatigue behavior of samples drawn from a prototype AM60 shock tower by conducting strain-controlled fatigue test along with X-ray computed tomography (XCT). The 3D analysis of porosity by XCT showed discrepancies from 2D metallographic characterization. Fatigue testing results showed the machined surface is the preferential site for crack initiation to occur, on which pores are revealed after specimen extraction. A large scatter in fatigue life was observed as crack initiating at a large pore situated on the surface will result in a significantly shorter fatigue life. SEM fractography showed fracture surfaces are generally flat and full of randomly orientated serration patterns but without fatigue striations. The observations and measurements of porosity and fatigue cracks made by XCT were confirmed by SEM, supporting it as a reliable characterization tool for 3D objects and has value in assisting the failure analysis by SEM. Fatigue life was found to decrease with the increase of fatigue-crack-initiating pore size. The same trend was also found between the fatigue life and the volume fraction of porosity. The pore shape and pore orientation should be taken into account when determining the pore size as they can result in the difference in pore size between 2D and 3D measurement.
Keywords: AM60 Mg alloy; High pressure die casting; X-ray computed tomography; porosity; fatigue